Procesos de elaboración de chifles de plátano y yuca - Sicchar Vilchez, Juan Andrés (2022)
In a process of manufacturing products for human consumption, it is important to know the attributes of the raw material to be processed —in the present work Musa paradisiaca L. [green plantain] and Manihot esculenta Crantz [cassava]— such as: the characteristics [taxonomic, physical, physicochemical, microbiological], nutritional value; as well as the parameters and unit operations to be developed for the elaboration of Chifles by frying by immersion in vegetable oil, giving them pleasant characteristics such as texture and aroma, uniformity in color and appearance; thus achieving the thermal destruction of the microorganisms and enzymes present and the reduction of the water activity, thus extending its useful life. Both processes can be carried out in an artisanal way or on an industrial scale, depending on the available resources since they do not require more technology than the basic assets for frying, utensils and packaging or, failing that, a greater implementation of automated machinery following the same technological principle. It is essential that these Chifles production processes are framed and conceived in the application of the HACCP Plan as a guarantee of control of dangers to the innocuousness that processed foods must have following the Peruvian health regulations.